The New Endemic Area of Schistosoma japonicum in Bada Highland Western Lore Subdistrict, District of Poso, Central Sulawesi Province - Sugiarto -; Soeyoko -; Sri Sumarni (Pusat Kedokteran Tropis, 2011)
Introduction: A new endemic area of schistosomiasis was discovered in Bada highland in 2008. Its prevalence in humans in the same year was 0.8%, and so far there is no studies about prevalence and characteristics of focus and human behavior related to the transmission of schistosomiasis in that area have been conducted.Objectives: To identify the prevalence of the disease caused by Schistosoma japonicum in humans, rats, and infection rate in snails. This study also described characteristics and human behaviors related to these characteristics and the history of visits to the endemic areas of Napu/Lindu.Methods: This study was a cross sectional survey. The prevalence of schistosomiasis in humans was identifi ed through stool examination by Kato Katz method. The prevalence in mice was estimated throughexaminations in dissected mice, and the identifi cation of cercariae in snails was done with crushing methods. Behavioral data were collected using questionnaires and focus characteristics were documented throughobservations. This research was part of the comprehensive study on schistosomiasis in Bada highland by Research and Development Center for Eradication of Disease of Animal Origin, Donggala.Results: The prevalence rate of schistosomiasis in humans was 5.93%, in rats 0% and in snails 1%. Types of focus were springs, ponds, irrigation channels, especially those with debris such as grasses, leaves, sticks dropped on the water. Prevalence rate in human was related to bathing in the river (p=0,00), entering the focus without protective shoes (p=0.034), defecation on the river (p=0,016). History of visit to endemicarea of Napu/Lindu was not associated with infection in human (p=0.344) and washing in the river was not associated also with human schistosomiasis (p= 0.521).Conclusion: The transmission of Schistosoma japonicum in a new endemic area of Bada highland is occurring and related to bathing, defecation in the river, and visit to the endemic focus without protectiveshoes.Keywords: Schistosoma japonicum, Bada highland, focus, transmission, Oncomelania